Community Psychiatric Nursing Services and Suicide Resilience in Selected Communities in the Greater Accra Region of Ghana - Buertey, A.A. (University of Ghana, 2023)
Background: Annually, 703,000 individuals end their own lives, with countless others attempting suicide. Each instance is a heart-breaking loss that deeply impacts families, communities, and nations, leaving lasting repercussions for those left behind. Several strategies can be implemented at the societal, sub-group, and individual levels to mitigate the occurrence of suicide and suicide attempts. Community resilience has been known and endorsed as a strategy for the management of suicide. However, not much is known about the use of community psychiatric nursing services as a strategy to promote community resilience against suicide. The aim of this study is to explore how to promote resilience against suicide in selected communities in the Greater Accra Region through community psychiatric nursing services. Methodology: The study employed a qualitative descriptive exploratory design in five (5) districts; Ningo Prampram, Ledzokuku, Ga East, Weija Gbawe and Ga South in the Greater Accra region. A semi-structured interview guide was used to collect data from eighty-nine (89) purposively selected participants. A purposive sampling technique was used to select eighteen (18) Community Psychiatric Nurses (CPN), thirteen (13) suicide attempters', seven (7) attempters' family members, four (4) family members of completed suicide cases, five (5) Focus Group Discussions with 46 participants and 1 Key Informant Interviews for the study. The data were transcribed verbatim after it has been audio recorded digitally. The data was analyzed using thematic analysis with MAXQDA 20. Data triangulation strategy was used to present the qualitative findings of the study. Results: The results showed that individuals who have attempted suicide in relation to precipitating factors included childhood experiences, psychiatric issues, mistrust, shame and disgrace, parental pressure, emotional breakdown, wasted resources, domestic violence, infidelity and difficult life pursuits. It was found that the response of suicide attempters’ families in relation to the general effects of the attempt on the family was Anger, shock, concern and solidarity. Also, the results showed that neutralizing the poison, inducing vomiting with the use of palm oil and crude oil, stoppage of bleeding, cutting down of noose, employing the services of skilled swimmers and calling of the police to be the means by which community members who almost lost/lost a member to suicide handled such cases. The results showed that Community Psychiatric Nurses have no laid down or specific guideline or policy in handling suicide cases. However, some of the strategies used by CPNs in the management of individuals and families of attempted and completed suicide cases were assessment, counselling and psychotherapy, medication, engaging the person/client in the area of interest, separating the person from the stressors, removing harmful items, physical monitoring and referral of cases that were beyond them to other health facilities. Furthermore, the results showed that the coping strategies used by families of suicide victims were through experience sharing and encouragement, relocating, social bonds, psyching oneself, acknowledging that tragedy may come to anyone, Word of God, Prayer and reliance upon God. Conclusions: Suicide is a very complex problem in the society, and there is general ignorance about the triggers, signs and appropriate help seeking strategies. Inadequate knowledge therefore tends to make individuals and communities less resilient to suicide. Community resilience to suicide can be significantly promoted if CPNs are provided with specific guidelines and retraining for the handling of suicide ideation and attempt. These guidelines and training coupled with provision of adequate funding and logistics, will enable the CPNs deliver high quality services to the suicide attempters, suicide attempter’s family, suicide bereaved families and also to intensify the general public education on the proper handling of all suicide related matters. A substantial number of community members are not aware of the existence of CPNs and therefore do not utilize their services. It is therefore imperative to create awareness about the existence and availability of CPNs through health education.
Research Article
Keywords: suicide; Community; psychiatric nursing services